2021
DOI: 10.1051/0004-6361/202141504
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the origin of magnetic perturbations associated with the FIP Effect

Abstract: Recently, magnetic oscillations were detected in the chromosphere of a large sunspot and found to be linked to the coronal locations where a first ionization potential (FIP) effect was observed. In an attempt to shed light on the possible excitation mechanisms of these localized waves, we further investigate the same data by focusing on the relation between the spatial distribution of the magnetic wave power and the overall field geometry and plasma parameters obtained from multi-height spectropolarimetric non… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 50 publications
1
3
0
Order By: Relevance
“…Numerical simulations by Dahlburg et al (2016) support the presence of the ponderomotive acceleration in solar coronal loops, with the appropriate magnitude and direction, and suggest it is a "by-product" of coronal heating. Recent work by Baker et al (2021), Murabito et al (2021), and Stangalini et al (2021) found magnetic fluctuations in the chromosphere being magnetically connected to regions of high FIP bias in the corona, which supports this theoretical model. More recent numerical simulations by Réville et al (2021) using a shell turbulence model found that, under the assumption that turbulence is the main driver of coronal heating and solar wind acceleration, a ponderomotive force can appear in the chromosphere and the transition region, and can be strong enough to create the FIP effect.…”
Section: Introductionsupporting
confidence: 64%
“…Numerical simulations by Dahlburg et al (2016) support the presence of the ponderomotive acceleration in solar coronal loops, with the appropriate magnitude and direction, and suggest it is a "by-product" of coronal heating. Recent work by Baker et al (2021), Murabito et al (2021), and Stangalini et al (2021) found magnetic fluctuations in the chromosphere being magnetically connected to regions of high FIP bias in the corona, which supports this theoretical model. More recent numerical simulations by Réville et al (2021) using a shell turbulence model found that, under the assumption that turbulence is the main driver of coronal heating and solar wind acceleration, a ponderomotive force can appear in the chromosphere and the transition region, and can be strong enough to create the FIP effect.…”
Section: Introductionsupporting
confidence: 64%
“…20 Dopplergram velocities were calibrated taking into account the orbital motion of SDO/HMI and the radial velocity of the Sun using the HMI ring diagrams available from JSOC. The mean Doppler velocity of each map is subtracted from all pixels within the map (Couvidat et al 2016;Murabito et al 2021).…”
Section: Consequences: Reconnection Outflow and Heatingmentioning
confidence: 99%
“…In Figure 7, we show an example of these maps from the start of the observing sequences on 2019 April 10, where for the IRIS 2 results we show the map of v turb at τ = −4.2 (typically the inversions are better constrained in the τ range ∼−3.8 to ∼−5). The choice of showing the v turb is motivated by both theoretical and observational results: the fractionation model of Laming (e.g., Laming 2015 and references therein) predicts a dependence of FIP bias on the magnetic waves propagating and/or reflecting in the chromosphere, and recent observations of a sunspot found Alfvénic waves associated with FIP bias enhancements (Baker et al 2021;Murabito et al 2021;Stangalini et al 2021). Assuming all the microturbulence comes from temporal unresolved Álfven waves, the time integration provides an upper limit of the frequencies, and the values of the microturbulence will be associated with the amplitude.…”
Section: Iris Chromospheric and Transition Region Properties And Rela...mentioning
confidence: 99%